Role of the proteasome in excitotoxicity-induced cleavage of glutamic acid decarboxylase in cultured hippocampal neurons - Baptista, Márcio (2010)
Glutamic acid decarboxylase is responsible for synthesizing GABA, the major inhibitory neurotransmitter, and exists in two isoforms--GAD65 and GAD67. The enzyme is cleaved under excitotoxic conditions, but the mechanisms involved and the functional consequences are not fully elucidated. We found that excitotoxic stimulation of cultured hippocampal neurons with glutamate leads to a time-dependent cleavage of GAD65 and GAD67 in the N-terminal region of the proteins, and decrease the corresponding mRNAs. The cleavage of GAD67 was sensitive to the proteasome inhibitors MG132, YU102 and lactacystin, and was also abrogated by the E1 ubiquitin ligase inhibitor UBEI-41. In contrast, MG132 and UBEI-41 were the only inhibitors tested that showed an effect on GAD65 cleavage. Excitotoxic stimulation with glutamate also increased the amount of GAD captured in experiments where ubiquitinated proteins and their binding partners were isolated. However, no evidences were found for direct GADs ubiquitination in cultured hippocampal neurons, and recombinant GAD65 was not cleaved by purified 20S or 26S proteasome preparations. Since calpains, a group of calcium activated proteases, play a key role in GAD65/67 cleavage under excitotoxic conditions the results suggest that GADs are cleaved after ubiquitination and degradation of an unknown binding partner by the proteasome. The characteristic punctate distribution of GAD65 along neurites of differentiated cultured hippocampal neurons was significantly reduced after excitotoxic injury, and the total GAD activity measured in extracts from the cerebellum or cerebral cortex at 24h postmortem (when there is a partial cleavage of GADs) was also decreased. The results show a role of the UPS in the cleavage of GAD65/67 and point out the deregulation of GADs under excitotoxic conditions, which is likely to affect GABAergic neurotransmission. This is the first time that the UPS has been implicated in the events triggered during excitotoxicity and the first molecular target of the UPS affected in this cell death process.